The Morphological Transformation of Indonesian: Impacts of Social Media and Globalization - Situmorang, Naila Izzatul Fikriyah; Anggraini, Nadia; Qonitah, Mutiara; Arini, Dian Widityastuti; Az-Zahra, Zafira; Erli, Ika Sucinta; Pebriana, Putri Hana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the phenomenon of morphological deviation in Indonesian that occurs in the digital era, especially in communication through social media and other digital platforms. Along with the development of information technology and globalization, Indonesian has undergone various changes, both in terms of understanding and morphological structure. This study uses a qualitative descriptive approach with corpus-based analysis techniques, to identify word forms that deviate from the standard rules of Indonesian. The results of the study show the emergence of various phenomena of morphological deviation, such as hybrid affixation, the use of non-standard reduplication and acronyms, and the compounding of foreign words without proper adaptation. In addition, this study also highlights the influence of social media on the evolution of Indonesian, where new terms such as “nge-chat”, “di-upload”, and “selfie” are increasingly used without an adjustment process that is in accordance with standard morphological rules. This phenomenon reflects the social and technological dynamics that drive changes in the way of speaking, and shows the importance of understanding morphology in the context of education and the development of language technology.